The Effect of Temperature and Cooking Time on Physical Stability and Quality of Kepundung Syrup - Elisa Julianti; Erman Munir; Gusik Lumiar (Postgraduate, University of Mataram, 2024)
Kepundung is a local fruit that grows almost on all island in Indonesia, the used of kepundung can be processed into fruit syrup. This research aims to determine the effect of temperature and cooking time on the physical stability and quality of kepundung syrup. This research began by making syrup made from kepundung fruit. The method used in this research is a factorial Completely Randomized Design method with two factors, that is cooking temperature (A): (80°C, 90°C, and 100°C) and cooking time (B): (20, 30, and 40 minute). The parameters tested in this research were color index stability (°Hue), pH, viscosity, organoleptic testing for 8 weeks, and thermal degradation kinetics. The results of the research showed that cooking temperature had a very significantly different effect (P<0.01) on the stability of the color index, pH, and viscosity. The best treatment for kepundung syrup is A3B3 (temperature 100°C and cooking time 40 minutes). Based on the determination of the kinetic ordo of thermal degradation, the color index R2 is closest to 1 at ordo 0 and in the calculation of Ea, ordo 0 is chosen with smaller Ea value. Based on determining ordo of thermal degradation kinetics, pH R2 closest to 1 at ordo 0 and in the calculation of Ea, ordo 1 is chosen with smaller Ea. Based on determining ordo of thermal degradation viscosity R2 is closest to 1 at ordo 1 and in the calculation of Ea, ordo 0 is chosen with smaller Ea